Phylogeny and taxonomy of the genus Cylindrocladiella - L. Lombard (2018)
The genus Cylindrocladiella was established to accommodate Cylindrocladium-like fungi that have small, cylindrical conidia and aseptate stipe extensions. Contemporary taxonomic studies of these fungi have relied on morphology and to a lesser extent on DNA sequence comparisons of the internal transcribed spacer regions (ITS 1, 2 and 5.8S gene) of the ribosomal RNA and the β-tubulin gene regions. In the present study, the identity of several Cylindrocladiella isolates collected over two decades was determined using morphology and phylogenetic inference. A phylogeny constructed for these isolates employing the β-tubulin, histone H3, ITS, 28S large subunit and translation elongation factor 1-alpha gene regions resulted in the identification of several cryptic species in the genus. In spite of the 18 new Cylindrocladiella species described in this study based on morphological and sequence data, several species complexes remain unresolved. © 2012 The Author(s).